Incidence of Vibrio parahaemolyticus at Estuarine Region of Sg. Sarawak (Sarawak) Influenced by Physicochemical Parameters - Lesley Maurice, Bilung (Hibiscus Publisher, 2014)
This study aimed to determine the correlation between physicochemical parameters namely salinity, pH and temperature with the occurrence of V. parahaemolyticus in estuarine river of Sg. Sarawak. A total of 72 water samples (surface and deep waters) were collected from the study site. A combination of MPN and PCR to detect and quantify the presence of V. parahaemolyticus, targeting the regulatory gene, toxR was performed. Over the 12-weeks sampling period, site 2 and site 3 recorded 100% presence of V. parahaemolyticus while site I was only 17%. The conditions found in site 2 (9.75‰, pH 7.2, 29.65 °C) and 3 (10.3‰, pH 7.36, 30 °C) favored the presence of V. parahaemolyticus (669 cells 10 ml-1 and 922 cells 10 ml-1 respectively) than site 1 (0.68‰, pH 6.75, 29.2 °C). Statistical analysis showed that the abundance of total V. parahaemolyticus counts was correlated well with the water salinity (Pearson correlation coefficient, r = 0.699; P < 0.01) and water temperature (r = 0.531; P < 0.01) but less correlated with water pH (r = 0.343; P < 0.01).